1942
DOI: 10.1042/bj0360460
|View full text |Cite
|
Sign up to set email alerts
|

The nutritive value of yeast protein: comparison of the supplementary values of yeast protein and casein for maize protein in the nutrition of the pig

Abstract: Since Osborne & Mendel [1919] found that rats thrived when given a diet containing brewer's yeast as sole source of protein, many investigators have further studied the nutritive value of yeast protein. Plimmer, Rosedale, Raymond & Lowndes [1934], in experiments on chickens, and Mitchell [1924a] in experiments on rats, found that yeast protein, when it is the sole source of nitrogen in the diet, is intermediate in nutritive value between the high value animal proteins and the poorer vegetable proteins; Thomas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1943
1943
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…It appeared in some instances that just before vomiting started there was excessive salivation, and possibly the vomiting may have been caused by choking from this excess saliva. It is significant to note that similar symptoms were observed by Macrae et al (1942) in their work on fodder yeast already referred to. They state that 'pig 2034 (5% yeast), pig 2168 (10% yeast) and pig 2080 (15 % yeast), were each observed to vomit on one occasion shortly after feeding, while pig 2167 (10 % yeast) vomited on two occasions.These animals may have vomited at other times.'…”
Section: Comments Onsupporting
confidence: 78%
See 2 more Smart Citations
“…It appeared in some instances that just before vomiting started there was excessive salivation, and possibly the vomiting may have been caused by choking from this excess saliva. It is significant to note that similar symptoms were observed by Macrae et al (1942) in their work on fodder yeast already referred to. They state that 'pig 2034 (5% yeast), pig 2168 (10% yeast) and pig 2080 (15 % yeast), were each observed to vomit on one occasion shortly after feeding, while pig 2167 (10 % yeast) vomited on two occasions.These animals may have vomited at other times.'…”
Section: Comments Onsupporting
confidence: 78%
“…Comments on Tables 7 and 8. The white-fish meal Macrae et al (1942) concluded that yeast proteins were not inferior to casein in supplementing the proteins in maize meal, and the results of the present trial confirm the high biological value, when yeast is incorporated in a barley meal-fine bran diet, for young pigs.…”
Section: B Balance Trials With 12 % Of Dried Brewers 1 Yeastsupporting
confidence: 73%
See 1 more Smart Citation
“…Sustainable protein alternatives are needed to reduce the dependency on soy and other conventional proteins as ingredients in the feed for animal husbandry. As early as in the 1940’s, researchers pursued the idea of replacing a substantial fraction of protein in animal feed with proteins from yeast derivatives [ 2 , 3 ]. It soon became apparent that the lack of cost efficient methods for large scale yeast production would limit the use of yeast proteins [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A marked supplementary effect of casein on the biological value of maize proteins for young growing pigs has been reported by Macrae et al (259).…”
Section: (Iv) Milk Proteinsmentioning
confidence: 72%